Solutions for small and medium-sized entreprises' difficulties in accessing finance: Asian experiences - Naoyuki Yoshino; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2017)
Small and medium-sized enterprises (SMEs) are the backbone of the Asian economy. They make up more than 96% of all Asian businesses that provide two out of three private sector jobs in the continent. Therefore, it is vitally important for the Asian economies' economic success that they have fully functioning support measures for SMEs. However, SMEs face major challenges in accessing cheap finance, mainly because there is an asymmetric information problem between suppliers and demanders of funds, which hinders their growth. This paper will highlight the difficulties of SMEs in accessing finance, and provides remedies for mitigating them. The remedies proposed in this paper include the development of credit information infrastructures for SMEs to remedy the asymmetric information problem, utilization of credit rating techniques for SMEs, the development of a sustainable credit guarantee scheme, the development of specialized private banks for SME financing, and the introduction of new ways of providing community-based financing such as hometown investment trust funds. The paper will provide operational examples from developed Asian economies such as Japan and the Republic of Korea, and developing Asian economies such as Thailand with a view to them being implemented in the rest of Asia.
Keywords: G21; G24; G32; 330; SMEs; Asian economies; credit rating; CRD; SME bank